The Role of Syncytin in Placental Angiogenesis and Fetal Growth - Wang, Ya-Nan; Ye, Yixin; Zhou, Da; Guo, Ze-Wen; Xiong, Zhelei; Gong, Xing-Xing; Jiang, Shi-Wen; Chen, Haibin (Frontiers in Cell and Developmental Biology, 2022)
Background: Syncytin, a retroviral envelope protein, is specifically expressed on trophoblast cells and mediates formation of the syncytiotrophoblast through fusogenic activity. Decreased expression of Syncytin was found in fetal growth restriction placentas. Results: By generating an inducible knockout of the syncytin-a gene in mice, we show a specific disruption of placental angiogenesis with abnormal formation of two syncytiotrophoblast layers. Consistent with the defects observed in vivo, conditioned medium collected from trophoblast cells, following Syncytin-1 knockdown, contains lower expression of vascular endothelial growth factor and placental growth factor, and higher levels of soluble fms-like protein kinase-1 in BeWo and HTR-8/SVneo cells which related with suppressed PI3K/Akt/mTOR pathway, and is reduced in ability to induce tube formation by HUVECs. Conclusion: Syncytin participates in angiogenesis during placental development was first identified both in vivo and in vitro. Here, we give a new sight on understanding syncytin and pathophysiology of placenta related disease such as fetal growth restriction.